P154 The improving lung cancer outcomes project: a study of the feasibility of a national reciprocal peer review and facilitated quality improvement programme. (2nd December 2011) - Jimenez, S; Martin, L; Aveling, E; Martin, G; Woolhouse, I
Abstract : Background: Variation exists in lung cancer outcomes in the UK, which does not appear to be wholly explained by differences in case mix. The Improving Lung Cancer Outcomes Project aims to address this via a 2 year programme of national reciprocal peer review and facilitated quality improvement. We describe the feasibility and acceptability of delivering this programme over the first year. Methods: All NHS trusts in England were invited to take part. Those who agreed were paired on the basis of contrasting results in four headline indicators from the national lung cancer audit. 15 pairs were randomised to the intervention arm and the remaining pairs acted as controls. The intervention group were invited to participate in workshops, reciprocal site visits, patient experience surveys and facilitated quality improvement (QI) work. Evaluation of this activity was performed using anonymous feedback, interviews with participants and observations of programme activities by external researchers. Results: 92 of 156 (59%) trusts agreed to participate. The site visits for the 15 pairs in the intervention arm took 6 months to complete and were attended by a total of 210 MDT members. The visits were seen as supportive yet opened up the possibility of legitimate challenge to existing ways of working. All 30 trusts in the intervention group were represented in the first patient survey, which had an overall response rate of 49%. However returns for individual trusts were low which reduced perceived credibility in some cases. 71 QI plans were submitted by 29 of the 30 trusts. These focused on a range of areas including data collection, diagnostics, and access to clinical nurse specialists. Considerable revision of the QI plans was required to ensure alignment with the overall project aims. Conclusions: We have demonstrated that reciprocal peer review and facilitated quality improvement planning is both feasible and acceptable as part of a national lung cancer improvement project. Organising timely site visits, providing credible patient feedback and maintaining the focus of quality improvement plans is challenging and requires considerable resource. The overall effect of the programme on patient experience and outcomes is awaited with interest.